The effect of Azolla species on growth response of flooded rice. - Fiore, Marli de Fátima; Bonetti, Roberto; Tsai, Siu Mui (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out under greenhouse conditions to assess the effect of seven different Azolla species on the growth of flooded rice using Azolla as an alternative source of nitrogen, incorporated into the soil of grown in dual culture. The treatments used were: no added nitrogen (control), 30 and 60 kg/ha of N, Azolla incorporated into the soil and grown in dual culture. Rice development was better using 30 and 60 kg/ha of N and when Azolla was incorporated into the soil. The A. caroliniana, A. filiciloides, A. mexicana and A. microphyllashowed good response. The results suggest the necessity of selecting Azolla species with a high potential as nitrogen source to flooded rice, as well as confirm their value as green manure for this culture.